Pancasila Sebagai Dasar Negara Indonesia - Jesika Indriani; Nurul Aisyah; Bambang Trisno (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Indonesia is a country that has a republican form of government based on Pancasila. The aim of the research is to determine the concept, position and function of Pancasila as the source of the Indonesian state. Research was obtained through the literature study method, namely by reading and searching from books, journals, laws and other relevant literature sources. with the problems contained in this journal. The research results show that Pancasila as the basis of the State means that every constitutional aspect of the Republic of Indonesia must be based on Pancasila values. This means that Pancasila must always be the spirit or power that animates activities in forming the State. The function of Pancasila is as a guide to life, in this function Pancasila has a role as the basis of every view that exists in Indonesia. Pancasila must be a guide in making one's own decisions in dealing with a problem. Pancasila is the soul of the nation, in this function Pancasila must be the soul of the Indonesian nation. Therefore, Pancasila must be realized in every institution, both organizations and individuals in Indonesia. Pancasila as the national personality, in this function Pancasila can also be called the identity of a gift from God that we must guard.